If $y = mx$ be the equation of a chord of a circle whose radius is \[a\] , the origin of coordinates being one extremity of the chord and the axis of $x$ being a diameter of the circle, prove that the equation of a circle of which this chord is the diameter is \[\left( {1 + {m^2}} \right)\left( {{x^2} + {y^2}} \right) - 2a\left( {x + my} \right) = 0\].
Answer
Verified
122.7k+ views
Hint-Equation of circle is \[{x^2}{\text{ + }}{y^2}{\text{ = }}{a^2}\] with centre at origin. The end points of the chord always lie on the circle and hence satisfy the circle equation.
According to question it is given that equation of chord is \[y = mx\]
So to solve this question first we assume the end of the chord be \[\left( {h,mh} \right)\] and the other end be \[\left( {0,0} \right)\]. These two end points of chords must lie on the circle.
Equation of circle is \[{\left( {x - a} \right)^2}{\text{ + }}{y^2}{\text{ = }}{a^2}\], and \[\left( {h,mh} \right)\] lies on the circle.
\[\therefore {\left( {h - a} \right)^2} + {m^2}{h^2} = {a^2}.....\left( {\text{i}} \right)\]
Now, expand the \[{\left( {h - a} \right)^2} = {h^2} + {a^2} - 2ha\] in the equation \[\left( {\text{i}} \right){\text{,}}\]
\[ \Rightarrow {h^2} - 2ah + {m^2}{h^2} = 0......\left( {{\text{ii}}} \right)\]
Take \[h\] common from above equation so that our equation simplifies further
\[
\Rightarrow h - 2a + {m^2}h = 0 \\
\Rightarrow h = \dfrac{{2a}}{{1 + {m^2}}} \\
\]
Now we got the value of $h$ which we can use to make the equation of the circle of which the chord is a diameter.
Therefore, the equation of circle of which chord $y = mx$ with endpoints \[\left( {0,0} \right){\text{ \& }}\left( {h,mh} \right)\] is the diameter will be
\[
(x - h)x + (y - mh)y = 0 \\
{x^2} + hx + {y^2} - mhy = 0 \\
{x^2} + {y^2} = h\left( {x + my} \right) \\
\]
Put $h$ value obtained as above
\[\left( {1 + {m^2}} \right)\left( {{x^2} + {y^2}} \right) = 2a(x + my)\]
Hence proved \[\left( {1 + {m^2}} \right)\left( {{x^2} + {y^2}} \right) = 2a(x + my) = 0\] is the equation of circle required.
Note-Whenever this type of question appears then always first write down the given things in the question. This is a very easy way to approach the question. Remember the standard equation of circle as mentioned in the solution which is \[{x^2}{\text{ + }}{y^2}{\text{ = }}{a^2}\]. The end points of a chord always lie on the circle hence, satisfy the circle equation.
According to question it is given that equation of chord is \[y = mx\]
So to solve this question first we assume the end of the chord be \[\left( {h,mh} \right)\] and the other end be \[\left( {0,0} \right)\]. These two end points of chords must lie on the circle.
Equation of circle is \[{\left( {x - a} \right)^2}{\text{ + }}{y^2}{\text{ = }}{a^2}\], and \[\left( {h,mh} \right)\] lies on the circle.
\[\therefore {\left( {h - a} \right)^2} + {m^2}{h^2} = {a^2}.....\left( {\text{i}} \right)\]
Now, expand the \[{\left( {h - a} \right)^2} = {h^2} + {a^2} - 2ha\] in the equation \[\left( {\text{i}} \right){\text{,}}\]
\[ \Rightarrow {h^2} - 2ah + {m^2}{h^2} = 0......\left( {{\text{ii}}} \right)\]
Take \[h\] common from above equation so that our equation simplifies further
\[
\Rightarrow h - 2a + {m^2}h = 0 \\
\Rightarrow h = \dfrac{{2a}}{{1 + {m^2}}} \\
\]
Now we got the value of $h$ which we can use to make the equation of the circle of which the chord is a diameter.
Therefore, the equation of circle of which chord $y = mx$ with endpoints \[\left( {0,0} \right){\text{ \& }}\left( {h,mh} \right)\] is the diameter will be
\[
(x - h)x + (y - mh)y = 0 \\
{x^2} + hx + {y^2} - mhy = 0 \\
{x^2} + {y^2} = h\left( {x + my} \right) \\
\]
Put $h$ value obtained as above
\[\left( {1 + {m^2}} \right)\left( {{x^2} + {y^2}} \right) = 2a(x + my)\]
Hence proved \[\left( {1 + {m^2}} \right)\left( {{x^2} + {y^2}} \right) = 2a(x + my) = 0\] is the equation of circle required.
Note-Whenever this type of question appears then always first write down the given things in the question. This is a very easy way to approach the question. Remember the standard equation of circle as mentioned in the solution which is \[{x^2}{\text{ + }}{y^2}{\text{ = }}{a^2}\]. The end points of a chord always lie on the circle hence, satisfy the circle equation.
Recently Updated Pages
JEE Main 2025 - Session 2 Registration Open | Exam Dates, Answer Key, PDF
The real roots of the equation x23 + x13 2 0 are A class 11 maths JEE_Main
Find the reminder when 798 is divided by 5 class 11 maths JEE_Main
Let A and B be two sets containing 2 elements and 4 class 11 maths JEE_Main
A ray of light moving parallel to the xaxis gets reflected class 11 maths JEE_Main
A man on the top of a vertical observation tower o-class-11-maths-JEE_Main
Trending doubts
JEE Main Login 2045: Step-by-Step Instructions and Details
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
JEE Main Chemistry Exam Pattern 2025
Physics Average Value and RMS Value JEE Main 2025
JEE Main 2023 January 25 Shift 1 Question Paper with Answer Keys & Solutions
Collision - Important Concepts and Tips for JEE
Other Pages
JEE Advanced 2025: Dates, Registration, Syllabus, Eligibility Criteria and More
JEE Main 2022 June 29 Shift 2 Question Paper with Answer Keys & Solutions
Clemmenson and Wolff Kishner Reductions for JEE
JEE Main Course 2025: Get All the Relevant Details
JEE Advanced 2025 Revision Notes for Practical Organic Chemistry
Free Radical Substitution Mechanism of Alkanes for JEE Main 2025